Research- and community-based clinicians' attitudes on treatment manuals. - Barry, Declan T; Fulgieri, Melissa D; Lavery, Meaghan E; Chawarski, Marek C; Najavits, Lisa M; Schottenfeld, Richard S; Pantalon, Michael V (The American journal on addictions / American Academy of Psychiatrists in Alcoholism and Addictions, 2008)
We assessed the attitudes of 18 research- and 22 community-based substance abuse clinicians on treatment manuals. Research and community clinicians exhibited favorable attitudes toward manuals, and the majority (72% and 77%, respectively) reported an interest in learning more about substance use disorder (SUD) treatment manuals. Among community clinicians, greater years of experience was significantly associated with less favorable attitudes toward treatment manuals. Research clinicians endorsed significantly higher ratings for the importance attached to "theoretical rationale/overview" and "main session points to address" than community clinicians. Findings suggest that community SUD clinicians are already familiar with and have positive attitudes toward manuals, but specific subgroups have concerns that should be addressed.
Keywords: Adult; Attitude of Health Personnel; Connecticut; Diffusion of Innovation; Evidence-Based Medicine; Female; Guideline Adherence; Humans; Male; Manuals as Topic; Middle Aged; Patient Care Team; Professional Competence; Research Personnel; Substance Abuse Treatment Centers; Substance-Related Disorders